2007
DOI: 10.1002/mds.21645
|View full text |Cite
|
Sign up to set email alerts
|

Primary lateral sclerosis mimicking atypical parkinsonism

Abstract: Primary lateral sclerosis (PLS), the upper motor neurone variant of motor neurone disease, is characterized by progressive spinal or bulbar spasticity with minimal motor weakness. Rarely, PLS may present with clinical features resembling parkinsonism resulting in occasional misdiagnosis as one of the atypical parkinsonian syndromes. Here we describe five patients initially referred with a diagnosis of levodopa-unresponsive atypical parkinsonism (n = 4) or primary progressive multiple sclerosis (n = 1), but sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Whether postural abnormalities of extrapyramidal origin are a characteristic of ALS patients with stiffness or may be found in ALS patients without stiffness remains to be determined, as well as the incidence of other extrapyramidal symptoms, such as bradykinesia. However, pyramidal involvement and spasticity may cause “pseudoakinesia” (i.e., slowness of repeated movements as finger tapping without fatiguing or decrement) 37. As in our study, shortening reaction test may allow to differentiate between true parkinsonian akinesia and movement slowness of pyramidal origin.…”
Section: Discussionsupporting
confidence: 60%
“…Whether postural abnormalities of extrapyramidal origin are a characteristic of ALS patients with stiffness or may be found in ALS patients without stiffness remains to be determined, as well as the incidence of other extrapyramidal symptoms, such as bradykinesia. However, pyramidal involvement and spasticity may cause “pseudoakinesia” (i.e., slowness of repeated movements as finger tapping without fatiguing or decrement) 37. As in our study, shortening reaction test may allow to differentiate between true parkinsonian akinesia and movement slowness of pyramidal origin.…”
Section: Discussionsupporting
confidence: 60%
“…It may be difficult to distinguish the clinical features of MND in the presence of parkinsonism and vice versa. For example, eminent authorities on PD18 described five patients who had been diagnosed with atypical parkinsonism and then PLS, and concluded that PLS could account for all clinical findings. We reviewed the videos included in the publication and noted hypomimia, profound bradykinesia, stooped posture, and prominent postural instability.…”
Section: Discussionmentioning
confidence: 99%
“…1 Pure PLS represents a more benign neurodegenerative condition thought to affect only upper motor neurons and is characterized with a better prognosis than amyotrophic lateral sclerosis (ALS). 2 For the clinician, PLS is a challenging diagnosis because it can mimic several disorders such as Parkinson disease, multiple systems atrophy, corticobasal syndrome, 3 neurofilament inclusion body disease, 4 and hereditary spastic paraplegia. 5 In PLS, functional neuroimaging can highlight selective upper motor neuron degeneration in areas such as the pericentral cortex 6 or primary motor cortex.…”
Section: Rimary Lateral Sclerosismentioning
confidence: 99%